Development of a real-time DOA estimation testbed - Zhang, Ning (2009)
Direction of Arrival (DOA) estimation is an essential parameter estimation in wireless systems and has many applications for defense and civilian purposes, such as source positioning, wireless communications, navigation, emergency aid, avalanche rescue. This project mainly focused on the development of a real-time DOA estimation testbed for testing various DOA estimation algorithms. The testbed consists of an array of antenna elements, a 4 channel oscilloscope, a notebook computer with GUI a graphical user interface (GUI) software developed with LabVIEW and Matlab. In this project, such DOA estimation methods like MUSIC and Watson-Watt are implemented and tested. The comparison of the two methods is discussed and recommendation for future development are suggested.